Revisitando o espaço escolar: os sentidos produzidos pelos professores sobre o SARESP na escola prioritária - Nogueira, Danielle Cristina (2015)
This study aims to understand the sense made by teachers about the external evaluation called SARESP (São Paulo State System of School Performance Evaluation) in a priority public school in São Paulo?s countryside. Theoretical support are used some authors who are dedicated to assessing the theme as Freitas, Barriga and Luckesi. In order to understand the meanings produced by teachers, this research opt for the qualitative methodology, case study, in which I propose to analyze the speeches of the subjects involved in this school context for understanding the relationship between the events described and the school failed, Since the school is considered a priority for the Secretary of Education of São Paulo (SEE-SP) due to low results obtained in SARESP. In this analysis I appropriate the concept of sense and meaning proposed by Vygotsky to understand from their comments, to the methodological construction of the research I appropriate to Lüdke, André and Certeau and discussion about school failure and use as a reference Esteban Patto. The data and analysis from the theoretical framework and statements of the teachers, signal the blame teachers for the results of this assessment creating a network of guilty that begins by category, but evolves in the use of their tactics to a larger share of blame for the Portuguese language and mathematics teachers. In the culprits game apex is the student himself in the individualization of failure, institutionalized as intellectual deficient. The data also led us to the need to understand what becomes the intellectual deficiency, understood as an element of materiality of school failure in this dissertation